Cosmic dawn : the search for the first stars and galaxies - Rhee, George (Astronomers' Universe, 2013)
The visible universe consists of stars and galaxies. One of the challenges of astronomy is to understand how galaxies and stars first came into existence over thirteen billion years ago. This book tells the story of our quest to solve this problem. Four hundred years after Galileo used his telescope to discover the  moons of Jupiter, we are using new telescopes and instruments to search for the first galaxies to form after the Big Bang. This book brings the reader to the current frontier of this subject and lays out some of the exciting developments we can expect in the years to come.